BRIDGING CULTURES THROUGH STORIES: ENHANCING SPEAKING SKILLS IN MULTICULTURAL ENGLISH CLASSROOMS - Khumukcham, Bishwajit; Mayanglambam, Buchi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper explores the role of storytelling as a powerful tool for language development in multicultural classrooms. By examining the intersection of language learning and cultural diversity, the study demonstrates how storytelling not only enhances language proficiency but also develops intercultural understanding and empathy among students from diverse backgrounds. Storytelling provides students with a contextual environment to practice English in a meaningful way, while encouraging them to share their unique cultural narratives. The paper discusses practical techniques for teachers to integrate storytelling into their lessons, including Cultural Show-and-Tell, Intercultural Dialogue, and Multilingual Storytelling. The findings highlight storytelling’s potential to build communication skills, expand vocabulary, and create an inclusive classroom environment. The paper concludes with recommendations for educators and suggestions for future research into the impact of storytelling on cultural understanding and language acquisition.